Image as a Propaganda Tool? Visual Representations ofthe ‘New Man’ in History Textbooks of the Socialist Era - Luku, Esilda (Contemporary Southeastern Europe)
This paper aims to analyze whether the images employed in national history textbooks inAlbania for the eight-year school under the socialist regime were used as a propagandatool to communicate the Party’s vision for the socialist transformation of society. It adoptsKress and Van Leuween’s visual socio-semiotic approach to examine the images in termsof their representational, interactive, and compositional meta-function. The findingsindicate that most of the images depict the “new socialist man,” who is willing to build upsocialism and defend the homeland; they have been represented close to the viewer, as thelatter belongs to the “new socialist society,” and the majority of the images place the “newman” in the center of the composition. Consequently, images in history textbooks servedthe state propaganda to manipulate and indoctrinate the young generation.